2008
DOI: 10.1016/j.acra.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Posture-dependent Human 3He Lung Imaging in an Open-access MRI System

Abstract: Effects of posture variation are observed, including posture-related effects of the diaphragm and distension of the lungs while vertical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
(159 reference statements)
0
11
0
2
Order By: Relevance
“…All participants (HV and ADDT) were only in the supine position for up to 20 min at a time during scanning and were upright between 129 Xe scans. Participants were encouraged to sit up and walk around between acquisitions and polarized xenon collections (~20 min) because previous studies confirmed that lung imaging results might not be a physiologically relevant after spending relatively long time in supine position . Therefore, we had to remove the patient from the scanner after each xenon dose or scan and relocalize (proton scan) the patient for the next xenon scan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants (HV and ADDT) were only in the supine position for up to 20 min at a time during scanning and were upright between 129 Xe scans. Participants were encouraged to sit up and walk around between acquisitions and polarized xenon collections (~20 min) because previous studies confirmed that lung imaging results might not be a physiologically relevant after spending relatively long time in supine position . Therefore, we had to remove the patient from the scanner after each xenon dose or scan and relocalize (proton scan) the patient for the next xenon scan.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were encouraged to sit up and walk around between acquisitions and polarized xenon collections (~20 min) because previous studies confirmed that lung imaging results might not be a physiologically relevant after spending relatively long time in supine position. 25,26 Therefore, we had to remove the patient from the scanner after each xenon dose or scan and relocalize (proton scan) the patient for the next xenon scan. Such approach likely led to a slight slice mismatch and potentially slight lung volume mismatch between the different xenon scans.…”
Section: Xe Mrimentioning
confidence: 99%
“…In-vivo 3 He MRI has been performed in human lungs at field strengths around 6 mT using homebuilt systems [39,17,16]. Our low-field system, which is designed to have very good field uniformity over a 5 Â 5 Â 5 cm volume, would be quite suitable for imaging rodent lungs.…”
Section: Advantages Of a Fully Phase-encoded Image Acquisitionmentioning
confidence: 99%
“…O aprimoramento das pesquisas e a evolução tecnológica fizeram surgir novas preocupações, relacionadas às mudanças do comportamento humano e seus efeitos sobre seu organismo, tais como as doenças cardíacas, responsáveis por 30% do total de mortes no mundo (27), e a obesidade, relacionada com os novos hábitos alimentares dos indivíduos e o aumento do sedentarismo da população em geral (25). Os efeitos da posição corporal na distribuição regional da ventilação/ perfusão motivaram pesquisas recentes, em especial pelas questões que envolvem o cuidado e a sobrevida de indivíduos com doenças pulmonares restritivas e obstrutivas (28).…”
Section: Revisão Histórica Dos Estudos Sobre a Função Respiratória E unclassified